2003
DOI: 10.1046/j.1464-5491.2003.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Type 1 diabetes of over 50 years duration (the Golden Years Cohort)

Abstract: Patients with long-duration (> 50 years) Type 1 diabetes are relatively protected from clinical diabetic nephropathy and large vessel disease; our data are consistent with protection possibly being genetically determined in part via elevated HDL-cholesterol levels. An abnormal urinary albumin/creatinine ratio is common in these patients, despite their low risk of significant renal deterioration; this may have implications for microalbuminuria screening programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
4
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 26 publications
6
87
4
4
Order By: Relevance
“…People with a diabetes duration of ≥ 50 years without previous CVD had significantly higher systolic blood pressure than those with previous CVD in the present study; however, ~84% of people with a history of such complications reported the use of antihypertensive medication. The corresponding proportion of those without previous CVD was ~62%, which is more than twice as high as the figures reported in the Golden Years cohort 9. This is somewhat surprising given that the mean age among people without complications in the present cohort was only 64 years, as opposed to 69 years in the Golden Years study, and is probably attributable to recent changes in risk factor treatment practices.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…People with a diabetes duration of ≥ 50 years without previous CVD had significantly higher systolic blood pressure than those with previous CVD in the present study; however, ~84% of people with a history of such complications reported the use of antihypertensive medication. The corresponding proportion of those without previous CVD was ~62%, which is more than twice as high as the figures reported in the Golden Years cohort 9. This is somewhat surprising given that the mean age among people without complications in the present cohort was only 64 years, as opposed to 69 years in the Golden Years study, and is probably attributable to recent changes in risk factor treatment practices.…”
Section: Discussioncontrasting
confidence: 70%
“…A previous cross‐sectional study of 400 people with > 50 years duration of Type 1 diabetes (the Golden Years cohort in the UK) suggested that they were relatively well protected from microvascular and macrovascular disease, possibly as a result of elevated HDL cholesterol levels 9. The present study showed significantly higher levels of HDL cholesterol in corresponding people who did not have a history of CVD at baseline.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Studies of long-term survivors reveal some consistent features [10][11][12][13][14]. For example, a clinical survey of 92 individuals who had survived for more than 40 years found that 30 had no detectable complications, 22 had 'minor' complications (mainly background retinopathy), 16 were blind or visually impaired, two had disabling neuropathy and eight had proteinuria.…”
Section: Look! We Have Come Through!mentioning
confidence: 99%
“…More men died than women, but not when corrected for relative mortality [11,12]. The more recent UK Golden Years study reports data collected by research nurses in the course of home visits, and provides indirect testimony as to the impact of laser therapy, for of the 400 50 year medalists, only 2% were blind [13]. The Joslin Medalist study reported questionnaire data on 326 similar individuals [14], and the two studies are compared in Table 1.…”
Section: At Age 10mentioning
confidence: 99%